Representing traffic congestions on moving objects trajectories - Kohan, Mariano (2015)
The discovery of moving objects trajectory patterns representing a high traffic density have been covered on different works using diverse approaches. These models are useful for the areas of transportation planning, traffic monitoring and advertising on public roads. Besides of the important utility, these type of patterns usually do not specify a difference between a high traffic and a traffic congestion. In this work, we propose a model for the discovery of high traffic flow patterns and traffic congestions, represented in the same pattern. Also, as a complement, we present a model that discovers alternative paths to the severe traffic on these patterns. These proposed patterns could help to improve traffic allowing the identification of problems and possible alternatives.